1973
DOI: 10.1159/000208392
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Factor X (Factor X Friuli) Coagulation Disorder

Abstract: A new case with the abnormal factor X (factor X Friuli) coagulation disorder is presented: a 32-year- old female who was born outside Friuli and who complained of a bleeding tendency since childhood. The main laboratory features are prolonged prothrombin time, prolonged partial thromboplastin time, abnormal thromboplastm generation and normal Stypven-cephalin clotting time. The prothrombin time and the thromboplastin generation were corrected by the addition of normal serum. Factor X was low only when assayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…After the description of the disease a few additional homozygote patients have been discovered in the same area [9,13,14,16]. One pa tient with a different geographical background has been described too, bringing the total to 11 patients.…”
mentioning
confidence: 99%
“…After the description of the disease a few additional homozygote patients have been discovered in the same area [9,13,14,16]. One pa tient with a different geographical background has been described too, bringing the total to 11 patients.…”
mentioning
confidence: 99%
“…Our patient with classical factor X deficiency had a factor X level of less than 0.1% and no detectable factor X protein was present in immu nological assays. On the contrary, the patient with factor X Friuli abnor mality had a factor X antigen of about 110% of normal and about 7% factor X activity using a tissue whole or partial thromboplastin [5,7]. It may, therefore, be concluded that neither factor X activity nor factor X antigen are necessary for platelet aggregation and adhesiveness.…”
Section: Discussionmentioning
confidence: 93%
“…Factor X deficient plasma was obtained from a patient pre viously reported [8]. Abnormal factor X (factor X Friuli) plasma was obtained from a patient previously reported [5]. The main features of these two patients are sum marized in table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far 11 homozygote patients and several heterozygotes have been reported [10,21,24]. The condition is transmitted as an au tosomal incompletely recessive trait [10,18,21,24], The main feature of the defect consists in the presence of an abnormal factor X which may not or may be activated only very slowly by whole or partial tissue thromboplastin whereas it may still be normally activated by Russell's Viper venom [7][8][9]16]. It was also demonstrated that prothrombin is normal in Friuli patients both as activity and as antigen [13] and that no inhibitor is present [17,22], Immunologically, factor X Friuli behaves as normal factor X both in plasma and is different from coumarin-induced abnormal factor X [15,19,23],…”
mentioning
confidence: 99%